Body Mass Index in Rural Indonesia: The Impact of Traditional Market Proximity, Age, and Gender - Syawaliyah, Ainun Nimah; Asyari, Aulya Rahmanisa Paramitha; Maulana, Taqwa Ziyan; Sulastijah, Siti; Farida, Dany; Candrasari, Anika; Firda, Fathiyyatu Assadiy; Romadhon, Yusuf Alam (Universitas Muhammadiyah Surakarta, 2024)
Purpose: Obesity is a growing public health problem in Indonesia, with prevalence influenced by several factors such as unhealthy diet, physical inactivity, and sociodemographic factors such as urbanization and socioeconomic status. It is associated with an increased risk of non-communicable diseases, including diabetes and asthma, and is more common in urban and affluent areas compared to rural areas. Although traditional markets may increase access to healthier food options, their direct impact on reducing obesity remains unclear. This study aims to conduct a multifactorial and bivariate analysis of obesity risk factors by involving analysis of the influence of gender, age, and traditional markets. Methodology: This cross-sectional study analyzed data on Gatak Sub-district Health Center visits (May-July 2024) and the presence of traditional markets from Statistics Indonesia reports, using Pearson Chi-Square and logistic regression to test the impact of age, gender, and market availability on BMI. Results: This study analyzed 9,639 patients, with fewer than half under 50 years old, two-thirds female, and nearly 80% living in areas without traditional markets. Multivariate and bivariate analyses revealed a higher proportion of obesity among patients aged 50 and older and females (p = 0.000). However, the presence of traditional markets showed no significant impact on obesity rates. The presence of traditional markets does not have a significant influence in causing obesity. Age 50 years and above and female gender have a higher risk of obesity. Applications/Originality/Value: This research contributes to understanding the factors that influence BMI in rural areas in Indonesia.